Carmagnani, M. (2021). Las conexiones del mundo y el Atlántico. - María Fernanda Martínez Muñoz (Investigaciones Geográficas, 2022)
Carmagnani, M. (2021). Las conexiones del mundo y el Atlántico. 1450-1850. El Colegio de México, Fondo de Cultura Económica. 279 pp., ISBN 978-607-167076-2.